The Influences of Environmental Knowledge, Word of Mouth (WOM), Green Marketing, and Environmental Care Attitude on the Purchase Intention of Green Products (A Study on Generation Z in Yogyakarta) - Achmad Kurniawan; Hanifa Nur Fadhilla (Eduvest - Journal of Universal Studies, 2024)
The research aims to test and analyze the influence of environmental knowledge, word of mouth (WOM), green marketing, and environmental care attitude on the intention to purchase green products. The population in this study is Generation Z in Yogyakarta. The sample size is 150 people, with the criteria of respondents being at least 18 years old, born between 1997 and 2012, residing in Yogyakarta, and having purchased and consumed green products. This study uses a quantitative method, with purposive sampling technique, and data analysis technique using Partial Least Squares Structural Equation Modeling (PLS-SEM) which is processed using SmartPLS 4.0 software. The results of the study indicate that environmental knowledge has a positive effect on the intention to purchase green products, word of mouth (WOM) has a positive effect on the intention to purchase green products, green marketing has a positive effect on the intention to purchase green products, and environmental care attitude has a positive effect on the intention to purchase green products.